Contextes d’un conte, pré-/prae- textes d’un détournement : Règlement de contes de Vera Feyder - Niedokos, Judyta (2023)
The present article aims to analyse Vera Feyder's text Règlement de contes by placing it in a vast French literary context and by highlighting the links that attach it to its praetexts - works on which it draws and which precede it. The examination carried out reveals that the play presented to the public in 1984 was written after the increased theoretical and literary interest in the tales of the 70s. On the other hand, its original form of radio broadcast revives the care to cultivate the oral tradition. The analysis of the work itself reveals the mix of sources with different generic membership as well as multiple levels of hypertextuality. The transformations introduced at the level of the constituent elements of the action make it possible to speak of the change in the motivations of the protagonists while the ideological and aesthetic scope of the story is focused on the spirit of resourcefulness and the universality of the genre. Consequently, the adaptation of tales proposed by Vera Feyder (Puss in Boots, Little Red Riding Hood and Sleeping Beauty by Charles Perrault and “Bon conseil aux amants” by Victor Hugo) falls under the art of palimpsest and makes it possible to classify it among the dramatic parodies of tales (according to Béatrice Ferrier's typology).
Keywords: Feyder Vera